2022
DOI: 10.5194/acp-22-12803-2022
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol size distribution changes in FIREX-AQ biomass burning plumes: the impact of plume concentration on coagulation and OA condensation/evaporation

Abstract: Abstract. The evolution of organic aerosol (OA) and aerosol size distributions within smoke plumes is uncertain due to the variability in rates of coagulation and OA condensation/evaporation between different smoke plumes and at different locations within a single plume. We use aircraft data from the FIREX-AQ campaign to evaluate differences in evolving aerosol size distributions, OA, and oxygen to carbon ratios (O:C) between and within smoke plumes during the first several hours of aging as a function of smok… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 87 publications
0
5
1
Order By: Relevance
“…A limitation of GOCART, however, is that the particle size distribution cannot vary in time or space for a given aerosol species. This contradicts the variability seen within particle size distribution during the low-level flight segment from CAMP 2 Ex RF9 as well as results from other field campaigns that indicate the particle size distribution of biomass burning aerosol changes with respect to median diameter and modal width as smoke ages (June et al, 2022). If the assumed particle size distribution for brown carbon in GEOS were to be modified such that the mode radius is larger, it would need to be thoroughly evaluated as a change in the particle distribution would also impact fields such as the single-scattering albedo and Ångström exponent.…”
Section: Discussioncontrasting
confidence: 96%
“…A limitation of GOCART, however, is that the particle size distribution cannot vary in time or space for a given aerosol species. This contradicts the variability seen within particle size distribution during the low-level flight segment from CAMP 2 Ex RF9 as well as results from other field campaigns that indicate the particle size distribution of biomass burning aerosol changes with respect to median diameter and modal width as smoke ages (June et al, 2022). If the assumed particle size distribution for brown carbon in GEOS were to be modified such that the mode radius is larger, it would need to be thoroughly evaluated as a change in the particle distribution would also impact fields such as the single-scattering albedo and Ångström exponent.…”
Section: Discussioncontrasting
confidence: 96%
“…Previous studies have concluded that coagulation has a larger effect on particle growth than OA evaporation/SOA formation, and coagulation rates are faster in denser plumes compared to more dilute plumes. 43,44,127 Using data from a scanning mobility particle sizer (SMPS) deployed at MBO during summer 2015, Laing et al 48 found both MSE and geometric mean particle diameter to be strongly correlated with plume concentration. Our results suggest that about 50% of the observed variability in MSE is explained by particle size (based on the R 2 between SAE and MSE), and that particle growth towards the measurement wavelength of 550 nm is more efficient in denser plumes.…”
Section: Resultsmentioning
confidence: 99%
“…Denser plumes from larger fires have slower dilution rates which favor coagulation and condensation, while less concentrated smoke from smaller fires is expected to have faster rates of dilution and evaporation, producing more SOA precursors. 42–44…”
Section: Introductionmentioning
confidence: 99%
“…As shown earlier, proper representation of aerosol size is also important for resolving MEE. Thus, given the correlation of diameter and refractive index, evaluating and developing models to resolve particle diameter (e.g., June et al., 2022) can also support parameterizations of real refractive index evolution.…”
Section: Resultsmentioning
confidence: 99%
“…Laboratory and field measurements have found a large range in mid‐visible MSE for fresh and aged smoke (1.5–6 m 2 /g for wavelengths on the 532–550 nm range), with values being correlated with changes in aerosol mean diameter as expected from Mie theory (Kleinman et al., 2020; Laing et al., 2016; Levin et al., 2010; J. S. Reid et al., 1998; J. S. Reid, Eck, et al., 2005). Aerosol size increase with age is the result of a combination of coagulation and gas‐to‐particle conversion of semi‐volatile material (Martins et al., 1996; J. S. Reid, Koppmann, et al., 2005), likely primarily coagulation (Hodshire et al., 2021; June et al., 2022).…”
Section: Introductionmentioning
confidence: 99%